PERTUMBUHAN DAN PRODUKSI VARIETAS SELADA (Lactuca sativa L) PADA BERBAGAI DOSIS PUPUK ORGANIK RUMPUT LAUT - Sulton Zainal Abidin; Oktavianus Lumban Tobing; Sjarif Avitidjadi Adimihardja (JURNAL AGRONIDA, 2017)
Lettuce (Lactuca sativa L.) is a widely known leave vegetable.  This vegetable is so rich in nutrient contents particularly vitamins and minerals that people can consume it to meet their nutrient requirements.  This study was aimed at assessing the effects of sea grass organic fertilizer administration on the growth and production of lettuce.  The study was conducted at the trial farm of Department of Agrotechnology, Faculty of Agriculture, Djuanda University, Bogor from March to April 2014.  A completely randomized design with two factors consisting of lettuce variety (V) and sea grass organic fertilizer (R) was used.  The varieties of lettuce consisted of curly lettuce (Lactuca sativa var. New grand rapid) (V1) and red lettuce (Lactuca sativa var. new red fire) (V2).  Sea grass organic fertilizer (R) was given in three levels, namely no fertilizer (R0), 500 kg/ha (0.5 recommended rate) (R1), 1000 kg/ha (1.0 recommended rate) (R2),  1500 kg/ha (1.5 recommended rate) (R3), and 2000 kg/ha (2.0 recommended rate) (R4).   Keywords: lettuce variety, sea grass organic fertilizer, growth and production.